Effects of different polypyrrole/TiO2 nanocomposite morphologies in polyvinyl butyral coatings for preventing the corrosion of mild steel - Mahmoudian, M.R.; Ebadi, M.; Alias, Y.; Basirun, Wan Jefrey (Elsevier, 2013)
This study addresses the synthesis and comparison of the corrosion protective properties of two different polypyrrole/TiO2 nanocomposite (PPy/TiO2 NC) morphologies in a polyvinyl butyral coating on mild steel. The polymerization was performed via low-temperature in situ chemical oxidative polymerization in the presence of methyl orange (MO) and dodecyl benzene sulfonic acid (DBSA). The field-emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) results show two different spherical and tube shapes in the core-shell structure of the PPy/TiO2 NCs synthesized in the presence DBSA and MO, respectively. The TEM results indicate that a thinner polypyrrole (PPy) shell is synthesized on the PPy/TiO2 NCs in the presence of MO than that synthesized in the presence of DBSA. Thermogravimetric analysis (TGA) results indicate that the mass percentages of the TiO2 NPs in the PPy/TiO2 NCs synthesized in the presence of MO and DBSA are 29.71 and 33.84%, respectively. The PPy/TiO2 NCs synthesized in the presence of MO were found to yield better anti-corrosion performance than those synthesized in the presence of DBSA. This result is due to the effect of the PPy surface area, which has more influence over corrosion control than the percentage of TiO2 nanoparticles in the nanocomposites. © 2012 Elsevier B.V. All rights reserved.